Behaviour of C-shaped angle shear connectors in high strength concrete / Ali Shariati - Ali, Shariati (2014)
The most commonly used types of shear connectors in steel-concrete composite structures are headed shear stud and Perfobond shear connectors. Due to the limitations in the performance of headed studs and Perfobond shear connectors, the use of Cshaped shear connectors as an alternative has been recommended. Furthermore, manufacturing of the C-shaped shear connectors is easier compared to the other connectors since in most steel shops, commercial standard sizes for hot rolled steel profiles of C-shaped shear connectors are available. Moreover, by simply cutting in their long steel profiles, these types of connectors can be easily prepared and the manufacturing cost and time for making C-shaped connectors are significantly low. Cshaped connectors show higher shear capacity and with the use of the conventional reliable welding system, it could be welded easily to steel beam. The angle connectors, as compared to channel connectors, could be cheaper and more economical due to the absence of bottom flange which ultimately saves more steel. The results of investigation of behavior of C-shaped angle shear connector is not included in previous research yet. In this thesis, the results of twenty four experimental push-out tests on angle shear connectors are presented. The connectors were embedded in a solid slab with High Strength Concrete (HSC) and were tested under monotonic and low cyclic fatigue loading. Based on the results, angle shear connectors showed good behavior in terms of shear strength but not in ductility as the main criterion for the behavior of shear connectors. Connector fracture types of failure was seen and less sensitivity to flange thickness and height of connectors was reported for angle connectors in terms of shear strength. Longer connectors exhibit more ductility compared to shorter connectors. The details of angle shear connector behavior have been discussed in detail as well.